A familial case of pachyonychia congenita - Bhengra, Masuma P; Choudhary, Ranju; Kumar, Prabhat; Chaudhary, Shyam Sundar (Journal of Pakistan Association of Dermatologists, 2016)
Pachyonychia congenita (PC) comprises a group of rare autosomal genodermatosis caused by mutation in any of the four genes KRT6A, KRT6B, KRT16 or KRT17. Classically, it is subdivided into two major variant types, PC-1 (Jadassohn-Lewandowski syndrome) and PC-2 (Jackson-Lawler syndrome). We hereby report a case of 22-year-old, married woman with progressive thickening and discoloration of all 20 nails, multiple, hyperkeratotic lesions present all over the body with oral lesions since childhood. She had a 2-month-old male baby (the only child) who presented with similar lesions of yellowish discoloration and nail thickening of both nails and foot since birth. She was diagnosed as PC type 1.